2020
DOI: 10.1371/journal.pone.0232233
|View full text |Cite
|
Sign up to set email alerts
|

Tyr-Trp administration facilitates brain norepinephrine metabolism and ameliorates a short-term memory deficit in a mouse model of Alzheimer’s disease

Abstract: The physiological actions of orally ingested peptides on the brain remain poorly understood. This study examined the effects of 39 orally administered synthetic Tyr-containing dipeptides on the enhancement of brain norepinephrine metabolism in mice by comparing the concentration of 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG). Although Tyr-Tyr administration increased blood and cerebral cortex (Cx) Tyr concentrations the most, Tyr-Trp increased Cx MHPG concentration the most. The oral administration of Tyr-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…To evaluate working memory, the Y-maze test was performed 6 days after the i.c.v. injection 68 (6 days of recovery is enough to get accurate behavior results as reported 10 , 11 , 12 , 13 , 14 , 15 , 16 ) ( Figures 3 , 4 , and S4 ). The maze was made of polyvinyl plastic and had three arms (395 mm depth, 120 mm height, 45 mm width at the bottom, and 100 mm width at the top), which were symmetrically disposed at 120° angles from each other.…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…To evaluate working memory, the Y-maze test was performed 6 days after the i.c.v. injection 68 (6 days of recovery is enough to get accurate behavior results as reported 10 , 11 , 12 , 13 , 14 , 15 , 16 ) ( Figures 3 , 4 , and S4 ). The maze was made of polyvinyl plastic and had three arms (395 mm depth, 120 mm height, 45 mm width at the bottom, and 100 mm width at the top), which were symmetrically disposed at 120° angles from each other.…”
Section: Methodsmentioning
confidence: 72%
“…Mice were housed in a specific pathogen-free controlled environment with a 12 h light/12 h dark cycle and constant temperature (25 °C) with under 4 mice per cage as previously described with some modifications. 68 All animal experiments were approved by the Animal Care and Use Committee of Nihon Bioresearch Inc., accredited by the Health Science Center for Accreditation of Laboratory Animal Care and Use of the Japan Health Sciences Foundation. All animal experimental procedures were performed in accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain natural foods containing neuroprotective peptides such as wheat, lantern fish, rice, walnuts, and soybeans, can be hydrolyzed by various enzymes. [95][96][97][98] To date, there has been little research into whether polypeptides isolated and identified from various animal or plant protein hydrolysates can be verified to have the capability of curing AD.…”
Section: Types and Sources Of Food-derived Anti-ad Peptidesmentioning
confidence: 99%
“…Although in this review, peptides crossing the BBB in intact form are discussed, little is known about their brain-benefit roles. Previous reports of di/tripeptides showing in vivo prevention effect of dementia are as follows: Leu-His (reduction of inflammatory cytokines in microglia) (Ano et al 2019a); Met-Lys-Pro (suppression of inflammatory cytokines and oxidative stress) (Min et al 2017); Trp-Tyr and Trp-Met (suppression of microglial inflammation) (Ano et al 2019b); Gly-Arg (increase of brain-derived neurotrophic factor and the number of neurons) (Katayama et al, 2014); Tyr-Trp, Ile-Tyr, and Ser-Tyr (upregulation of catecholamine metabolism) (Ichinose et al 2015& Ichinose et al, 2020Moriyasu et al 2016); Tyr-Leu, Phe-Leu, Trp-Leu (activation of anxiolyticrelated receptors) (Mizushige et al 2013); and Tyr-Pro (promotion of acetylcholine production) (Tanaka et al 2020). However, to recognize di/tripeptides as brain-beneficial food compounds, further research is required in the following years to clarify the mechanism(s) of BBB transportation and accumulation in brain parenchyma.…”
Section: Perspectivementioning
confidence: 99%